Dianthibiological aspects of one fungi rhizoctoniaand its in vitrointeraction withfusarium oxysporum f. sp.dianthi (2002)
ABSTRACTGrowth in different culture media and temperature as well as its antagonic roleagainst Fusarium oxysporumSchlencht f. sp. dianthi(Prill and amp; Del) Snyder and amp; Hansen, werestudied on an isolated of the fungi Theobroma grandiflorum(Spreng) K. Schum. Lowgrowth and the presence of abundat moniloid cells were detected when the fungi wascultured in PDA in microculture, with natural light and at 20ºC. Higher temperatures(27ºC and 30ºC) increased growh rate. When cultured at 20ºC, in darkness, similarresults as those recorded at 30ºC in natural light were found. After a month sclerotiagrotwh was present. Culture in AMS in Petri dishes, with natural light at 20ºC showedgrowth in patches which suggests phenotype variability. Poor growth was recordedwhen cultured in AAg. Our results showed that rapid and vigorous growth isobtanined when the fungi is cultured in PDA at 30ºC in darkness producing conidiaand sclerotia. T. grandiflorumalso has an antagonic role against F.oxysporumsp. dianthi,growing faster and inihibitingits growth.